2018
DOI: 10.1080/07448481.2018.1469503
|View full text |Cite
|
Sign up to set email alerts
|

Designing effective point-of-choice prompts to promote active transportation and staircase use at a Canadian University

Abstract: This study provides insights for designing suitable point-of-choice prompts that are tailored for university students in terms of future interventions that aim to improve their activity levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 35 publications
(57 reference statements)
0
10
0
Order By: Relevance
“…The uptrend in active transportation in USA may be related to a number of strategies, such as the construction of cycle paths, car restriction, car-free days, and so on [22,28]. Similar strategies have been implemented in other countries [21,29], such as Canada, Australia, etc.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The uptrend in active transportation in USA may be related to a number of strategies, such as the construction of cycle paths, car restriction, car-free days, and so on [22,28]. Similar strategies have been implemented in other countries [21,29], such as Canada, Australia, etc.…”
Section: Discussionmentioning
confidence: 99%
“…In view of mounting evidence on the health benefits of walking and cycling, some countries encouraged residents to increase transportation-related physical activity (such as walking or cycling to and from work) to improve individual health and to reduce air pollution, carbon emissions, traffic dangers, and other harmful impacts of car use. In Canada, suitable point-of-choice prompts were designed for university students to promote active transportation [21]. In the United States, community infrastructures were developed to support physical activity, such as sidewalks and bicycle trails [22].…”
Section: Introductionmentioning
confidence: 99%
“…The authors of these studies also showed that the mode of transportation is conditioned by particularities of university campuses such as bike share systems [58], tailored and strategically-placed point-of-choice prompts, through which students should switch to active transportation [59], or the distribution of the university scheduled classes on the days of the week [60]. However, in order to make use of the potential to increase cycling among students Grimes and Baker (2020) [58] revealed that bike share systems conditions in university settings must be tailored to the target group, Chim et al, (2020) [60] pointed out that there is only a positive association of university courses on weekdays with more time spent cycling if students cycle to classes anyway, and Irwin (2019) [61] showed that uncontrollable factors for example time, built environment, and weather affected the participation in activities. Thus, just like the results of our study, these findings show that the combination of environmental conditions and personal psychological determinants is important to consider.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous further typical small-scale studies on stair promotion signs have been published. These include stair signs in university settings (Crozier et al, 2019;Engelen 2017;Ly et al, 2019), metro stations (Allias et al, 2017), an airport (Bellettiere et al, 2017), and a city centre office building (Bennett et al, 2018). These studies have continued to reinforce that the magnitude of change in stair use following the installation of a sign is broadly consistent with what has been reported in previous studies.…”
Section: Text Boxmentioning
confidence: 99%